Relationships within the Melitaea phoebe species group (Lepidoptera: Nymphalidae): new insights from molecular and morphometric information. (11th June 2014) - TÓTH, JÁNOS P.; BERECZKI, JUDIT; VARGA, ZOLTÁN; ROTA, JADRANKA; SRAMKÓ, GÁBOR; WAHLBERG, NIKLAS
Abstract The genus Melitaea consists of about 80 species, divided into ten species groups, which are all restricted to the Palaearctic region. The Melitaea phoebe group was defined by Higgins based on morphological characters such as wing pattern and genital structures. According to his interpretation, the M. phoebe group included seven species: M. phoebe, M. sibina, M. scotosia, M. aetherie, M. collina, M. consulis and M. turkmanica. The taxonomy of the phoebe species group has been poorly resolved and recent results on the species composition within the group suggest the need for a re‐evaluation. In this study molecular sequences (5985 bp) including one mitochondrial (COI) and up to six nuclear (CAD, EF‐1α, GAPDH, MDH, RpS5 and wingless) gene regions from 38 specimens of the Melitaea phoebe species group sensu Higgins and some closely related taxa from the Palaearctic region were analysed. The possible evolution of the processus posterior of the male genitalia was also reconstructed based on a shape mapping technique. The analysis of the combined data shows a very clear pattern and almost all relationships are highly supported. Based on the combined Bayesian tree and the shape of the processus posterior of the male genitalia, four main groups are recognised: (i) collina group, (ii) arduinna group, (iii) aetherie group and (iv) phoebe group. The status of M. ornata, M. zagrosi and M. scotosia as species is confirmed, and the results also indicate that M. telona (s.s.) from Israel is a separate species.